PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SD PADA PEMBELAJARAN IPA - Suyit Ratno; Mutiara Lubis; Etika Suri; Feby Surya Handari; Lamria Siringoringo (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2022)
Critical thinking skills are part of the important things that must be mastered by students in facing challenges in the 21st century. This aims to improve problem solving skills. Critical thinking skills mean getting used to seeking the truth of all information obtained by finding out and exploring this information through valid data. This research method is a literature review. This study aims to find out that the application of the Project Based Learning learning model can improve elementary students' critical thinking skills. In this learning the teacher acts as a facilitator so that students are more directed at the freedom to build their own knowledge so that the learning that takes place is more meaningful.